2008
DOI: 10.1063/1.2980045
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport and spin-polarization effects of relativisticlike particles in mesoscopic graphene structures

Abstract: Motivated by recent studies on the use of graphene for new concepts of electronic/spintronic devices, the authors develop an efficient calculation method based on the nonequilibrium Green’s function to solve the quantum relativisticlike Dirac’s equation that governs the low-energy excited states in graphene. The approach is then applied to investigate the electronic transport and the spin polarization in a single-graphene barrier structure. The obtained results are presented and analyzed in detail aiming to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Several different mechanisms by which NDC can be generated in graphene-based devices have been modelled theoretically, for example, 31827. The observation of NDC in a graphene field effect tunnel transistor in which the current flows along the graphene layer was also reported recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different mechanisms by which NDC can be generated in graphene-based devices have been modelled theoretically, for example, 31827. The observation of NDC in a graphene field effect tunnel transistor in which the current flows along the graphene layer was also reported recently.…”
Section: Discussionmentioning
confidence: 99%
“…Devices based on these materials have been investigated in a number of recent experimental and theoretical papers2345678910111213141516171819202122232425262728. By fine-tuning the composition of the stacks, it may be possible to create materials with novel electronic and optical properties, which outperform conventional semiconductors.…”
mentioning
confidence: 99%
“…Due to ambipolar transport behavior of Graphene, NDR has been observed and reported in various three terminal GNR devices [14]. Previously single-gate Graphene sheet junctions have also shown negative differential resistance [15]. Negative differential resistance was also discovered in arm chair GNR junction [16,17], and the arm chair GNR junction has been examined for its suitability in tunneling diodes [17].…”
Section: Introductionmentioning
confidence: 98%
“…[15][16][17][18][19][20][21][22][23][24][25][26], but there are a few theoretical studies for these subjects in silicene. 12,[27][28][29][30][31][32][33][34][35] Giant magnetoresistance (GMR) in a zigzag silicene nanoribbon connecting to two silicene sheets has been predicted by Xu et al 12 Using first principle calculations, Tsai et al have shown that a gated silicene quantum point contact can be used a tunable spin polarizer with 98% spin polarization.…”
Section: Introductionmentioning
confidence: 98%